Observation of Markarian 421 in TeV gamma rays over a 14-year time span - Acciari, V. A. (2014)
The variability of the blazar Markarian 421 in TeV gamma rays over a 14-year time period has been explored with the Whipple 10 m telescope. It is shown that the dynamic range of its flux variations is large and similar to that in X-rays. A correlation between the X-ray and TeV energy bands is observed during some bright flares and when the complete data sets are binned on long timescales. The main database consists of 878.4 hours of observation with the Whipple telescope, spread over 783 nights. The peak energy response of the telescope was 400 GeV with 20% uncertainty. This is the largest database of any TeV-emitting active galactic nucleus (AGN) and hence was used to explore the variability profile of Markarian 421. The time-averaged flux from Markarian 421 over this period was 0.446$pm$0.008 Crab flux units. The flux exceeded 10 Crab flux units on three separate occasions. For the 2000-2001 season the average flux reached 1.86 Crab units, while in the 1996-1997 season the average flux was only 0.23 Crab units.